Is cardiovascular fitness a risk factor for ALS? - Turner, M (BMJ Publishing Group, 2017)
The association between ALS and reduced cardiovascular disease is hypothesis-generating, driving novel pathway discovery, and not necessarily secondary to premorbid physical activity.